1995
DOI: 10.1002/art.1780381214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress management on clinical outcomes in rheumatoid arthritis

Abstract: Objective. To examine the effects of stressmanagement training on clinical outcomes in persons with rheumatoid arthritis (RA). Methods.Patients with RA (n = 141) were randomly assigned to 1 of 3 groups: a stress management group, an attention control group, or a standard care control group. The stress management and the attention control groups received a 10-week intervention followed by an additional 15-month maintenance phase.Results. The stress management group showed statistically significant improvements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
1
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(135 citation statements)
references
References 38 publications
(13 reference statements)
4
128
1
2
Order By: Relevance
“…Length of the interventions varied from 3 days to 9 months with a mean of 9.8 weeks. One study (38) utilized a "refresher" course following the actual intervention. Nineteen of the 25 studies collected followup data with followup time periods ranging from 2 to 18 months (mean of 8.6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Length of the interventions varied from 3 days to 9 months with a mean of 9.8 weeks. One study (38) utilized a "refresher" course following the actual intervention. Nineteen of the 25 studies collected followup data with followup time periods ranging from 2 to 18 months (mean of 8.6).…”
Section: Resultsmentioning
confidence: 99%
“…Five of the 25 studies (30,37,41-43) described a proper method of randomization (e.g., table of random numbers, computer generated). Patients were deemed to be blind to the treatment condition in 5 trials (27,30,37,38,43), although as noted earlier, such blinding is typically either not possible or not ethical in many behavioral interventions. Following von Tulder et al (20), in studies that utilized an attention control as the placebo condition, we considered patients to be blind if the researchers performed a treatment credibility analysis and there were no significant differences between the intervention or control group in terms of the participants' assessment of credibility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These protocols have been shown to be effective for patients with rheumatoid arthritis and osteoarthritis in randomized, controlled clinical trials (24,25). Recent studies of cognitive-behavioral therapy (CBT) protocols have shown positive findings in patients with FMS (26).…”
Section: Chronic Pain Segmentmentioning
confidence: 99%